Northern Lights Instead of Workers’ Rights: Volunteer Working Tourists in Finnish Lapland - Brennan, Christopher (Nordic Journal of Working Life Studies, 2018)
Research on volunteers in the tourism field often deals with the motivations of such persons as well as their effects on host locales, while research on the work conditions of tourism workers often focuses solely on paid employees. However, such research has not focused on the workplace conditions for volunteer working tourists in the tourism arena whose motivation, among other reasons, for seeking unpaid work opportunities is a dual role of tourism consumer. As volunteers are not formally employed, they are not entitled to legal workplace standards. This article examines, through netnographic research methods and thematic analysis, the workplace experiences of several volunteer working tourists in Finnish Lapland, considering how similar to precarious employment their situation is, to some extent enabled by their tourism mindset. This raises curious questions about the use of such labor, suggesting their future inclusion within discussions of precarious work